The Role of Teachers in Disciplining Students During Congregational Prayers at Washilatul Al-Ikhlas Mosque - Siregar, Rosmaini; Sormin, Darliana; Siregar, Adek Kholijah (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study aims to examine the role of teachers in disciplining students during congregational prayers at the Washilatul Al-Ikhlas Mosque of MAN 1 Padangsidimpuan and to identify the challenges faced by teachers in this process. The research employs a descriptive qualitative approach, which seeks to systematically describe facts and characteristics of the studied object while emphasizing the meaning derived from the collected data. Data were gathered through observation, interviews, and documentation. The analysis followed the Miles and Huberman qualitative model, consisting of data reduction, data display, and conclusion drawing/verification, carried out interactively until the data reached saturation. The findings reveal that teachers play a crucial role in motivating, guiding, and setting an example for students in performing congregational prayers. Teachers act not only as supervisors but also as active participants, thereby serving as role models for students. Student discipline is reflected in their punctuality in performing prayers, their sense of solidarity, and their effective use of time. The challenges encountered include the large number of students, limited mosque capacity, and the inability of teachers to provide comprehensive supervision. Nevertheless, the overall implementation of congregational prayers at MAN 1 Padangsidimpuan is orderly and effective in fostering religious awareness and building students’ disciplined character.